Sarcoidosis: Psychotherapy and Long-Term Outcome—A Case Report - Giancarlo Trombini; Elena Trombini (Case Reports in Medicine)
Sarcoidosis is a systemic, inflammatory disease of unknown aetiology, influenced by stressful life events and associated with a high incidence of alexithymic personality traits, and of depressive symptoms. The medical literature on sarcoidosis has called for a psychotherapeutic intervention to modify the perceived state of disease, the influence of stressful events and the depressive condition. Few studies have described cases treated with psychotherapy, and no information is available on its long-term outcome. We present the case of a patient with chronic sarcoidosis and periodical reacutizations with constantly pathological ESR. Twenty-four years after the diagnosis, a dynamic supportive-expressive psychotherapy for psychosomatic alexithymic patients was added to the medical therapy. At the beginning and at the end of the psychotherapy, and for the long-term outcome evaluations, Kellner’s symptom questionnaire (SQ) was used to investigate psychological distress. The SQ scores, initially pathological, were normal at the end of the psychotherapy and for the following three years. Psychotherapy, without antidepressive drugs, resolved the depression. The depressive symptoms disappeared, along with the normalization and stabilization of the ESR. After three years, the outcome was positive. This is the first study describing a successful psychotherapy and its long-term outcome on a patient with sarcoidosis.